Diversity and characteristics of colonization of root-associated fungi of Vaccinium uliginosum. Issue 1 (December 2018) - Yang, Hongyi; Zhao, Xingyu; Liu, Changli; Bai, Long; Zhao, Min; Li, Lili
Abstract This study investigated ericoid mycorrhizal fungi (EMF) diversity inVaccinium uliginosum across its main wild distribution range in China. Fungal communities in hair roots ofV .uliginosum were analyzed using Illumina MiSeq sequencing. Only 22 OTUs were assigned to putative EMF genera.Rhizoscyphus andMeliniomyces dominated EMF communities, followed byClavaria, Oidiodendron, Lachnum, Acephala, andPhialocephala . There were more dark septate endophytes (DSE) reads from the Greater Khingan Mountains than from other study areas, similar to the results of the percent colonization of DSE by the magnified intersections method. Overall, high-throughput sequencing data provided a rough community-scale sketch of root-associated fungi ofV .uliginosum . Two hundred and eighty slow-growing isolates were isolated from root pieces ofV .uliginosum, and the isolates matched 16 fungal genera on the basis of morphological and internal transcribed spacer sequence comparison. The isolates ofCryptosporiopsis ericae, Oidiodendron maius, Lachnum sp., Sordariomycetes sp., andPleosporales sp., formed ericoid hyphal coils via resynthesis trails. The co-existence between EMF and DSE in hair roots was observed via trypan blue staining. A putative model for the co-existence between EMF and DSE in the hair roots ofV .uliginosum was proposed. We suggest that under certain environmental stresses, such as low temperature and poor available nutrients, ericoid plants may favor co-colonization by both DSE and EMF.